Sportlight on faculty member: Dr. Mohammad Amin - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Safriza, Baharuddin; Muhammad Najib, Muhammad Nor; Noor Azhar, Abd. Rasid
Dr. Muhammad Amin, 38 years old, was bom in Pinrang, Sulawesi. Indonesia. He became interested in chemistry while in secondary school in Sulawesi. After receMng his bachelors degree in chemistry from Hasanuddin Universi1y (Makassar). Dr. Amin spent six years at Gifu Universi1y, first completing a masters and then doctoral work in analytical chemistry, specializing in ion exchange chromatography. He joined Universiti Malaysia Pahang on 29 September 2008 bypassing an opportuni1y for postdoctoral study at Yokohama Universi1y.